Procedural Sedation in Minor Procedure Rooms for Pediatric Myringotomy and Tympanostomy: A Quality Improvement Initiative. (December 2022) - Roy, Catherine F.; Turkdogan, Sena; Nguyen, Lily H. P.; Yeung, Jeffrey
Objective: Lengthy wait times for elective surgery is a widespread health care system conundrum that may increase patient distress and jeopardize health outcomes. The primary aim of this quality improvement project was to reduce the surgical wait time in patients undergoing tympanostomy tube insertion. Methods: As of January 2018, our tertiary care institution implemented a novel protocol whereby healthy children may undergo tympanostomy tube insertion in a minor procedure room under ketamine sedation administered by pediatric emergency physicians to address lack of both physical and anesthesia staffing resources. A retrospective study of all children undergoing elective tympanostomy tube insertion was conducted between September 1, 2017, and May 8, 2019, to assess wait time to surgery, as well as anesthesia-related and surgical complications. Results: Procedural sedation in minor procedure rooms effectively decreased surgical wait times by 53 days (from 134 to 81 days, P < .001) at 16 months postimplementation. This new protocol was found to be safe and effective for healthy children, with no major surgical or anesthesia-related complications noted in 113 patients having undergone the procedure in the novel setting. Discussion: Although conscious sedation by emergency physicians has been well studied across a variety of surgical procedures, its novel use in pediatric tympanostomy tube insertion requires careful patient selection to enhance accessibility while maintaining anesthetic safety. Implications for Practice: This quality improvement project describes a novel combination of processes, using a minor procedure room space and ketamine-based procedural sedation to address surgical wait times in pediatric patients undergoing tympanostomy tube insertion.